MEASURING THE PERFORMANCE OF SDGS IN PROVINCIAL LEVEL USING REGIONAL SUSTAINABLE DEVELOPMENT INDEX - Thamrin, Nurafiza; Wulansari, Ika Yuni; Irawan, Puguh Bodro (UI Scholars Hub, 2023)
Measuring the national and sub-national progress in achieving such globally adopted development agendas as Sustainable Development Goals (SDGs) is particularly challenging due to data availability and compatibility of indicators to measure SDGs, especially in Indonesia. This paper attempts to measure the performance of sustainable development at the regional level in Indonesia by newly constructing a multidimensional composite index called the Regional Sustainable Development Index (RSDI). RSDI comprises four dimensions, covering comprehensive economic, social, environmental, and governance indicators. By applying factor analysis, the paper assesses the uncertainty of RSDI and the sensitivity of its composing indicators, then further investigates the relationship between RSDI and the Human Development Index (HDI). RSDI is proven to have high precision with low uncertainty. A significantly positive relationship between RSDI and HDI suggests a consistent direction between both progresses (0.7726). RSDI in Indonesia can be categorized as medium-high level, with two provinces (East Nusa Tenggara and Papua) having low RSDI. RSDI helps identify provinces with the latest progress in SDG performance, allowing the government to prioritize interventions for provinces lagging behind.